2017
DOI: 10.1111/fcp.12265
|View full text |Cite
|
Sign up to set email alerts
|

Bufalin, a bufanolide steroid from the parotoid glands of the Chinese toad, inhibits L‐type Ca2+ channels and contractility in rat ventricular myocytes

Abstract: Bufalin is a bufanolide steroid compound in Chan Su. Chan Su is a traditional Chinese medicine prepared from the dried white secretion of the auricular and skin glands of toads and has been used as an oriental drug. However, the effect of bufalin on cardiac function and its underlying cellular mechanisms remain unclear. Here, we explore the cellular mechanisms of bufalin on myocardial protection via the whole-cell patch-clamp recording and video-based edge detection system. Exposure to bufalin resulted in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Bufalin is a kind of cardiac glycosides which is derived from the serous fluid secreted by the parotid venom glands and skin of Bufo melanostictus and Bufo bufo gargarizans [20]. Researches have showed that Bufalin has many pharmacological activities, including anti-inflammatory, anti-tumor, antiviral, cardiotonic and narcotic effects [21][22][23][24]. Among these effects, the anti-tumor activity of Bufalin has caught the attention of many researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Bufalin is a kind of cardiac glycosides which is derived from the serous fluid secreted by the parotid venom glands and skin of Bufo melanostictus and Bufo bufo gargarizans [20]. Researches have showed that Bufalin has many pharmacological activities, including anti-inflammatory, anti-tumor, antiviral, cardiotonic and narcotic effects [21][22][23][24]. Among these effects, the anti-tumor activity of Bufalin has caught the attention of many researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, LTCCs blockers generally protect against myocardial ischemic injury via the inhibition of calcium channels. Previous studies have emphasized the inhibitory effect of verapamil (VER) on myocardial contraction and the protective effect on excess calcium overload (Song et al, ). Hence, drugs that can weaken I Ca‐L are promising for myocardial protection (Song et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Bufalin (C 24 H 34 O 4 ) is one of the main active components of Chan Su . In our previous study, we have found that bufalin can inhibit the L‐type Ca 2+ channels and contractility in rat ventricular myocytes . However, some studies have also shown that bufalin has cardiotoxic effects and can increase the risk of cardiac arrhythmia , but studies that have demonstrated cellular mechanisms of arrhythmia caused by bufalin are limited.…”
Section: Introductionmentioning
confidence: 99%